Exploration of Dating Violence and Related Attitudes Among Adolescents and Emerging Adults - Courtain, Audrey (Journal of interpersonal violence, 2021)
Young people’s romantic relationships can be marked with various forms of dating violence (DV). However, adolescents and emerging adults do not necessarily acknowledge this violence because of their attitudes toward dating violence. Our study aims to study dating violence and attitudes toward this phenomenon through two well-established questionnaires administered jointly in their entirety. Indeed, too many studies report results on some dimensions and items, neglecting the richness of available tools. The Conflict in Adolescent Dating Relationship Inventory and the Attitudes Toward Dating Violence Scale were self-administered to 1,014 participants (M age = 18.9) attending secondary schools or a regional college. They reported the frequency of their dating violence perpetration and victimization, and their attitudes toward dating violence. Results show that relational and sexual violence perpetration rates are higher for males, physical violence perpetration rate is higher for females, and relational violence victimization is higher for males. MANCOVAs not only show the same trends for scores but also underline more frequent emotional violence perpetrated by females, physical victimization for males, and sexual victimization for females. Males show higher tolerance toward every form of dating violence; younger participants are also more tolerant. Participants are more tolerant toward male-perpetrated psychological DV than female-perpetrated ones, and more tolerant toward female-perpetrated physical and sexual DV compared with male-perpetrated physical and sexual DV. There are patterns of multiperpetration, multivictimization, bidirectionality, and multi(in)tolerance. Our paper contributes to the symmetry debate, a better understanding of the link between attitudes and violent behaviors, a further step on gendered attitudes regarding who perpetrates and who sustains.